Effect of opponent quality on goal-patterns from direct play in Japanese professional soccer - Miyazawa, T.; Keika, M.; Sheahan, J. P.; Ichikawa, D. (International Journal of Sports Science, 2017)
The quality of the opponent is considered an important factor that can influence attacking performance in soccer. Despite this, it is unknown whether the quality of the opponent has an influence on the effectiveness of direct attack goal scoring and its characteristics. The aim of this study was to determine the influence of league ranking which is one of opponent quality on the percentage of goals scored by direct attack of all goals based on the analysis of Japanese professional soccer league (J-League) in 2016. We also validated the effect of opponent quality on the characteristics of direct attack. In order to accomplish this aim, all goals from open play were divided into two categories based on league-table position at the end of season of the team from which the goal was scored: goals scored against inferior position teams (IN-goals) and superior position teams (SU-goals). Furthermore, these goals were divided into two attacking styles: direct and elaborate attack. For the comparison of characteristics of direct attack, further analysis was conducted on three variables toward goals scored by direct attack: passes per possession, possession duration and possession starting zone. The number and percentage of goals scored by direct attack in IN-goals was 130 goals and 37.6% and significantly lower than those in SU-goals (89 goals and 46.8%). There was no difference in distribution of the characteristics between IN- and SU-goals. Our findings suggest that effectiveness of direct attack for goal scoring become higher against superior opponent quality. In contrast, the characteristics of direct attack were not affected by opponent quality. Direct attack with two passes, duration of 10 seconds or less and starting at the offensive half is thought to be common among the goal scoring against superior and inferior opponents in order to improve goal scoring ability.